1968
DOI: 10.1002/pol.1968.150060601
|View full text |Cite
|
Sign up to set email alerts
|

Polyisonitriles. II. Heterophasic catalytic synthesis of poly(α‐phenylethylisonitrile) and of poly(n‐hexylisonitrile)

Abstract: synopsisA three-component catalytic system has been discovered, which successfully polymerizes a-phenylethylisonitrile to high polymer ( D P = 200-900) and also polymerizes n-hexylisonitrile. The catalyst componqnts ate a strong acid, a free-radical source, and a heterophase and are all necessary in this system. The use of a liquid medium in which the polymer is insoluble promotes the rate of polymerization and total yield. Poly-(a-phenylethylisonitrile), formed from monomer in a presence of oxygen and finely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1970
1970
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…These bands in Figure A are tentatively ascribed to the presence of imine groups on the surface, −NC<, and are the result of a stretching mode, ν (−NC<) . Imine groups could only come about on the surface through reactions of the isocyanide moieties with each other to form polymeric isocyanides, otherwise known as poly(iminomethylenes), [R−NC<] n . , To verify that the bands between 1580 and 1680 cm -1 were due to poly(iminomethylenes), clean Au surfaces were exposed to methanolic solutions of chemically synthesized poly(diisocyanohexane) for 24 h. The resulting RAIR spectrum is shown in Figure B. The resemblance in Figure between parts A and B in the 1580−1680 cm -1 region is striking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These bands in Figure A are tentatively ascribed to the presence of imine groups on the surface, −NC<, and are the result of a stretching mode, ν (−NC<) . Imine groups could only come about on the surface through reactions of the isocyanide moieties with each other to form polymeric isocyanides, otherwise known as poly(iminomethylenes), [R−NC<] n . , To verify that the bands between 1580 and 1680 cm -1 were due to poly(iminomethylenes), clean Au surfaces were exposed to methanolic solutions of chemically synthesized poly(diisocyanohexane) for 24 h. The resulting RAIR spectrum is shown in Figure B. The resemblance in Figure between parts A and B in the 1580−1680 cm -1 region is striking.…”
Section: Resultsmentioning
confidence: 99%
“…Millich first synthesized polyisocyanides or poly(iminomethylenes), over 20 years ago from isocyanide monomers in the presence of O 2 (an initiator) and finely ground glass coated with sulfuric acid (a catalyst). 22a,b Later, he demonstrated that the use of glass coated with small quantities (10 -2 mequiv g -1 ) of relatively weak acids (p K a ∼2) can result in higher yields of much larger molecular weight polymers 22c. It was suggested that the glass surface provides an environment that is conducive to the polymerizationa supported, highly concentrated, physisorbed isocyanide layerby reducing the unfavorable entropy change associated with bringing bulky groups together and by acting as a solid-phase support for the production of insoluble [R−NC<] n 22d. This was the major synthetic route to polyisocyanides for many years until transition-metal-catalyzed polymerizations were realized 15a.…”
Section: Resultsmentioning
confidence: 99%
“…Polyisocyanides constitute such a class of macromolecules and have been studied extensively in the past. [4][5][6] These macromolecules contain the repeat unit shown here [7] and can be obtained, among other methods, by polymerization of isocyanides with acid [8] or a Ni II catalyst. [9] The polymers fold into a 4 1 -helical conformation (i.e., residue 5 is on top of residue 1) that can slowly be converted into a random coil structure, depending on the side chain R. [10][11][12] Polyisocyanides derived from a-amino acids are particularly interesting because their helical backbone is stabilized by the formation of "b-sheet"-like hydrogen-bonding arrays between peptide side chains n and n + 4; [13] this results in well-defined and very rigid polymers, as reflected by the persistence length, which exceeds that of double-stranded (ds) DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(iminomethylenes) (PIM), also named polyisocyanides, are a class of synthetic polymers which has received considerable attention in the recent past. They contain the repeating unit shown in Scheme and are prepared from the corresponding isocyanides mostly by cationic polymerization (both protonic and Lewis acids have been used as initiators), or by coordination polymerization employing transition metal compounds, in particular those of Ni(II). ,, Several PIM bearing different side chains (R) have been synthesized to date (for reviews of synthetic methods see refs −9). They have shown some practical use, for instance in nonlinear optical materials , or as chiral stationary phases in liquid chromatography .…”
Section: Introductionmentioning
confidence: 99%
“…Poly(α-phenylethyl)iminomethylene was one of the first polymers of this class thoroughly investigated by the school of F. Millich. ,, On the basis of the examination of space-filling molecular models, the authors proposed that a rational structure of the above polymer could be a tightly coiled helix , The 4 1 helical structure has often been attributed to all poly(iminomethylenes). However, lately, experimental evidence for the occurrence of stereo irregularity in the chain of some PIM was reported, as for instance, in poly(( S )-2,2-dimethyl-1,3-dioxolanyl-4-methyl isocyanide), and in poly(( S )-1-cyclohexylethyl isocyanide) .…”
Section: Introductionmentioning
confidence: 99%